Perancangan Web-GIS (Website Geographic Information System) Kabupaten Lebong - Endri Agustomi (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2021)
Abstract In the era of globalization with the level of technological progress in various sectors requires the use of technology to be one part of various activities. Both in terms of production, management, and even government. Everything that is done quickly and efficiently does require an additional tool which in this case is the sophistication of the technology it self. Engaged in the government sector, the Lebong Regency Government has begun to run the government using technology, one of which is in the field of information technology. Development and use of government areas is an important thing so that it can be examined properly. The effectiveness of performance is required in carrying out this matter. Information technology that can be utilized in government, one of which is “Geographic Information System” (GIS). Using GIS will be very effective in promoting effective and efficient governance. Remote sensing that can broadly observe land makes Lebong Regency Government activities even better.